Evelyn Waugh's satire : texts and contexts - Milthorpe, Naomi (Fairleigh Dickinson University Press, 2016)
"Waugh is a perennial subject for literary scholars; most studies published in the past thirty years take a strongly biographical approach, using Waugh's life and faith as lenses through which to critique the fiction. Evelyn Waugh's Satire takes a different approach: using frameworks of modernist studies, intertextuality, satire theory, and the contexts of the interwar period, Milthorpe renews debates about the targets and tactics of Waugh's satire."--